2016
DOI: 10.1159/000443564
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Model of Intervertebral Disk Mediated Postoperative Epidural Fibrosis

Abstract: Background: Postoperative epidural fibrosis (EF) after lumbar discectomy is the most common and at the same time controversial issue. Purpose: The etiology and pathogenesis creates a lot of discussion and selection of methods of treatment and prevention continues. Methods: LIV laminectomy with dura mater (DM) exposition was done in 24 rats, and then, 0.3 ml of elements of suspension of autologous intervertebral disk was implicated on DM. As autologous intervertebral disk, we used the intervertebral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 11 publications
(10 reference statements)
0
9
0
2
Order By: Relevance
“…Because fibroblast adhesion and the combined cellular response contribute to various aspects of wound healing, many studies have been conducted to clarify the adhesion mechanism of fibroblasts in these tissues. Mechanisms including enhanced collagen synthesis by fibroblasts that migrated from paraspinal muscles, inflammation triggered by intervertebral disc fibroblasts, and activated interleukin‐6 expression due to angiopoietin‐like protein 2 binding in ligamentum flavum fibroblasts have been proposed …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because fibroblast adhesion and the combined cellular response contribute to various aspects of wound healing, many studies have been conducted to clarify the adhesion mechanism of fibroblasts in these tissues. Mechanisms including enhanced collagen synthesis by fibroblasts that migrated from paraspinal muscles, inflammation triggered by intervertebral disc fibroblasts, and activated interleukin‐6 expression due to angiopoietin‐like protein 2 binding in ligamentum flavum fibroblasts have been proposed …”
mentioning
confidence: 99%
“…Mechanisms including enhanced collagen synthesis by fibroblasts that migrated from paraspinal muscles, inflammation triggered by intervertebral disc fibroblasts, and activated interleukin-6 expression due to angiopoietin-like protein 2 binding in ligamentum flavum fibroblasts have been proposed. 12,13 Because wound healing in epidural tissue is closely linked to the reaction to inflammation in dura mater cells, several efforts have been made to investigate this relationship. Studies using mini-pigs and rabbits revealed that most cultured dura mater cells are fibroblasts.…”
mentioning
confidence: 99%
“…Secondary operations required because of EF are both challenging and have a high complication rate[ 1 , 3 , 4 ]. Braverman et al[ 40 ] reported a success rate of only 30%-35% in operations performed by them to correct EF and observed adverse results in 10%-20% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…EF causes reoccurrence of symptoms because of post-operation nerve root tensioning or compression[ 2 ]. A second operation is often required to remove scar tissue, and it is both difficult and has a high rate of complications[ 1 , 3 , 4 ]. A majority of authors believe that to avoid surgical treatment, EF should be prevented before it occurs[ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Target genes were amplified using the Power SYBR® Green Master Mix (Invitrogen Life Technologies Corporation, Carlsbad, CA) and the Applied Biosystems 7900HT Fast Real-Time PCR System. Target gene expression was quantified using the relative standard curve method [ 19 ], using a standard curve generated with serial dilution (1 : 5) of a pool of aliquots of sample cDNA, and subsequently normalized to glyceraldehyde 3-phosphate dehydrogenase (GAPDH) gene expression. Primers, designed to span exon-exon boundaries to avoid amplification of genomic DNA, were used for analyzing established parameters of HF and markers of fibrosis.…”
Section: Methodsmentioning
confidence: 99%